2012
DOI: 10.1128/ec.00211-12
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular NADPH Levels Affect the Oligomeric State of the Glucose 6-Phosphate Dehydrogenase

Abstract: In the yeast Kluyveromyces lactis, glucose 6-phosphate dehydrogenase (G6PDH) is detected as two differently migrating forms on native polyacrylamide gels. The pivotal metabolic role of G6PDH in K. lactis led us to investigate the mechanism controlling the two activities in respiratory and fermentative mutant strains. An extensive analysis of these mutants showed that the NAD ؉ (H)/NADP ؉ (H)-dependent cytosolic alcohol (ADH) and aldehyde (ALD) dehydrogenase balance affects the expression of the G6PDH activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 43 publications
0
36
0
Order By: Relevance
“…The appearance of the I G6PDH band is strictly correlated to the intracellular accumulation of NAD(P)H [17]. In contrast, when the S. cerevisiae cellular extracts were run and stained for G6PDH activity in native PAGE, they showed only one band, independently of growth conditions, (Fig.…”
Section: G6pdh Is a Component Of Putative Macromolecular Proteins Strmentioning
confidence: 89%
See 1 more Smart Citation
“…The appearance of the I G6PDH band is strictly correlated to the intracellular accumulation of NAD(P)H [17]. In contrast, when the S. cerevisiae cellular extracts were run and stained for G6PDH activity in native PAGE, they showed only one band, independently of growth conditions, (Fig.…”
Section: G6pdh Is a Component Of Putative Macromolecular Proteins Strmentioning
confidence: 89%
“…1, lane 4), two bands when cells were grown in fermentative conditions or in the presence of ethanol (Fig. 1, lane 3) and many bands (lane 5) when the same strain was transformed with the plasmid containing the wild type ZWF1 gene, coding for the G6PDH, fused to the GFP gene [17].…”
Section: G6pdh Is a Component Of Putative Macromolecular Proteins Strmentioning
confidence: 99%
“…G6PDH is a component of dynamic macromolecular depot structures in S. cerevisiae. The oligomeric state of G6PDH is affected by intracellular NADPH levels; G6PDH activity is under strong feedback inhibition by NADPH [40,41]. In addition, NADPH is a product of G6PDH.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that G6PDH was allosterically regulated by NADPH/NADP + ratio [56,67] and sterols [59,67]. In coldblooded animals, G6PDH was shown to be reversibly phosphorylated/dephosphorylated [70].…”
Section: Superoxide Dismutasementioning
confidence: 99%